(untitled) (Applied Biological Research, 2017)
Investigations were conducted at PAU, Ludhiana (India) during 2014 and 2015 to assess the effect of foliar application of boron @ 110, 220 and 440 pm and 2,3,6-tri-iodo-benzoic acid (TIBA) @ 100, 200 and 400 ppm on oil yield and fatty acid profile of staggered sown (January 20, February 10 and March 2) spring sunflower. Studies revealed that delayed sowing reduced oil content and yield with concomitant increase in protein content. Increase in oleic acid with concomitant decrease in palmiticand linoleic acids was also noted as the sowing was delayed. Foliar application of boron and TIBA did not influence the oil content and its fatty acid composition but caused significant improvement in protein content and oil yield. Correlation studies revealed that oil content, oil yield and linoleic acid were highly significant (p<0.01) but negatively correlated with canopy temperature. Oleic acid was positively correlated with canopy temperature. It may be concluded that early sowing by 20th January and application of boron 110 ppm or TIBA 100 ppm gavis higher oil yield while maintaining good oil quality.